2016
DOI: 10.1159/000445226
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dyspepsia and Gastroparesis

Abstract: Background: Upper gastrointestinal disorders typically present with common symptoms. The most relevant non-mucosal diseases are gastroparesis, functional dyspepsia and rumination syndrome. The literature pertaining to these 3 conditions was reviewed. Key Messages: Gastroparesis is characterized by delayed gastric emptying in the absence of mechanical obstruction of the stomach. The cardinal symptoms include postprandial fullness (early satiety), nausea, vomiting and bloating. The most frequently encountered ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 58 publications
0
36
0
1
Order By: Relevance
“…The most pronounced sour taste primarily attained to the old tradition. Together with the sensory attributes, the perception of appetite, satiety and gastrointestinal symptoms is essential to assess food digestibility because tightly correlated with gastric emptying and intestinal fermentation [13,14]. It must be highlighted that the present study aimed at investigating bread digestibility in healthy subjects, acting as reference group for further studies on subjects with upper GI symptoms such as bloating, reflux, epigastric pain or irritable bowel syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most pronounced sour taste primarily attained to the old tradition. Together with the sensory attributes, the perception of appetite, satiety and gastrointestinal symptoms is essential to assess food digestibility because tightly correlated with gastric emptying and intestinal fermentation [13,14]. It must be highlighted that the present study aimed at investigating bread digestibility in healthy subjects, acting as reference group for further studies on subjects with upper GI symptoms such as bloating, reflux, epigastric pain or irritable bowel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to define univocally the concept of bread digestibility from a nutritional perspective seems controversial. Indeed, bread digestibility relies on factors of different nature: the perception of appetite, satiety and gastrointestinal symptoms after ingestion [13][14][15], and the bioavailability of proteins and starch. A few in vivo clinical studies have already demonstrated the effect of sourdough fermentation on starch digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…Further, functional dyspepsia was noted in one‐third of nausea sufferers in our study. Functional dyspepsia frequently presents with nausea and upper abdominal discomfort and symptoms which overlap with those of gastroparesis . These entities are difficult to distinguish clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal studies are beginning to demonstrate the utility of implantable devices to record GI function, leading to proof-of-concept studies using miniaturized, wireless, and closedloop device configurations [3]. Significant questions remain before these novel methods can be translated to the clinic, including (1) how many signals are needed to assess specific functions of the GI tract, (2) how to compensate for the intrinsic variability of GI anatomy and electrode placement between individuals, and (3) what features within the GI myoelectric signal are associated with functional changes in the GI system, such as nausea or digestion.…”
Section: Introductionmentioning
confidence: 99%